Sexual Behavior Patterns and PrEP Dosing Preferences in a Large Sample of North American Men Who Have Sex With Men. (1st January 2016) - Stack, Conor; Oldenburg, Catie; Mimiaga, Matthew; Elsesser, Steven A.; Krakower, Douglas; Novak, David S.; Egan, James E.; Stall, Ronald; Safren, Steve; Mayer, Kenneth H.
Abstract : Introduction: Pre-exposure prophylaxis (PrEP), taken as a single daily coformulated pill containing tenofovir -emtricitabine, is a promising intervention to reduce the likelihood of HIV acquisition in at-risk individuals, including men who have sex with men. Little is known about the acceptability of less than daily, intermittent PrEP regimens. Methods: We conducted an online survey of North American men who have sex with men to characterize their sexual frequency and planning behaviors and correlate these with PrEP dosing preferences. Results: Of the 3217 respondents who completed the survey, 46% reported engaging in unplanned condomless anal intercourse (CAI) at least once in previous 3 months and 8% reported engaging in CAI more than once per week. In multivariable analysis, reporting unplanned CAI was associated with lower educational level, identifying as homosexual/gay as compared with bisexual, being in a monogamous relationship, having a higher self-perceived risk of HIV acquisition, reporting higher income, engaging in CAI more than five times in the last 3 months, and not having visited a health care provider in the previous year. Frequent CAI (>1 time per week) was associated with being younger, identifying as homosexual/gay as compared with bisexual, being in a monogamous relationship, and having a higher self-perceived risk of HIV. Having only planned sex over the last 3 months was associated with a preference for event-based PrEP, whereas having frequent or unplanned CAI was associated with a preference for daily or time-driven PrEP regimens, respectively. Conclusion: Our findings suggest that preferences for different PrEP regimens are associated with the sexual frequency and planning behaviors of potential users. Abstract : Supplemental Digital Content is Available in the Text.